2017
DOI: 10.1177/1010428317691683
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of miR-145-5p in NSCLC and potential molecular mechanism exploration: A retrospective study based on GEO, qRT-PCR, and TCGA data

Abstract: MicroRNAs have been reported to be involved in various biological processes. Here, we performed a systematic analysis to explore the clinical value and potential molecular mechanism of miR-145-5p in non-small cell lung cancer. First, a meta-analysis was performed with eligible literature, followed by microRNA microarrays in the Gene Expression Omnibus database, to verify the diagnostic and prognostic values of miR-145-5p. A cohort of 125 clinical paired non-small cell lung cancer samples was next used to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…miR-145-5p is down-regulated in many types of cancer including cervical cancer, non-small cell lung cancer (NSCLC), colorectal cancer and ESCC, and functions as tumor suppressor in carcinogenesis [ 5 , 8 , 20 , 21 , 22 , 23 ]. Metadata showed that the expression of miR-145 was significantly lower in NSCLC than that in healthy tissues, and miR-145 tended to show better diagnostic performance in lung squamous cell carcinoma than in lung adenocarcinoma [ 24 ]. In ESCC, the expression of miR-145 was significantly associated with tumor invasion [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-145-5p is down-regulated in many types of cancer including cervical cancer, non-small cell lung cancer (NSCLC), colorectal cancer and ESCC, and functions as tumor suppressor in carcinogenesis [ 5 , 8 , 20 , 21 , 22 , 23 ]. Metadata showed that the expression of miR-145 was significantly lower in NSCLC than that in healthy tissues, and miR-145 tended to show better diagnostic performance in lung squamous cell carcinoma than in lung adenocarcinoma [ 24 ]. In ESCC, the expression of miR-145 was significantly associated with tumor invasion [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many miRNAs are overexpressed in NSCLC tissues, but have low expression in the adjacent normal tissues, called proto-oncogenes. Additionally, several miRNAs are found to be under-expressed in the NSCLC tissues, which are considered as “anti-oncogenes” 6 , 7 , 8 . Furthermore, miRNAs which target multiple genes and different groups of target genes of the same miRNA are often regulated mutually.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ACTG1 has been reported to exhibit high expression levels in skin cancer tissue, where it may regulate A431 cell proliferation and migration via the Rho-associated protein kinase signaling pathway (25). ACTG1 has also been predicted to be a target gene of miR-145-5P in non-small cell lung cancer (26). Furthermore, ACTG1 and matrix metalloproteinase 14 (MMP14) were validated as targets of miR-10a in colorectal cancer cells; ectopic expression of ACTG1 and MMP14 may delay decreases in cell adhesion and anoikis resistance activity (27).…”
Section: Discussionmentioning
confidence: 99%